Descriptive analysis of the implementation of gender responsive policies for poverty alleviation in Aceh - Inayatillah, Inayatillah; Musdawati, Musdawati; Fitri, Cut Dian; Mardhiah, Nelli (Universitas Islam Negeri Ar-Raniry, 2025)
Women’s poverty in Aceh persists due to entrenched gender norms restricting their economic access and social welfare, despite the poverty alleviation efforts. Gender mainstreaming policies (GMP), initiated through Presidential Instruction No. 9/2000, remain ineffective due to weak institutional coordination, inadequate funding, and exclusion of women in planning. This qualitative study analyzes policy implementation via document reviews, observations, and interviews, revealing multidimensional challenges. Institutional fragmentation, short-term program focus, and financial constraints limit women’s empowerment. Women’s exclusion from policy planning further reduces program ownership and engagement. Field data underscore women’s undervalued economic roles in coastal and agricultural sectors. In fishing communities, women contribute to fish processing, while female coffee farmers in Bener Meriah manage harvesting and small businesses. However, restricted access to resources, credit, and decision-making stifles their potential. To address these gaps, the study advocates strengthening institutional collaboration, increasing gender-responsive budgets, and integrating women into planning and evaluation. Sustainable outcomes require prioritizing long-term strategies with robust monitoring. Enhancing resource access, financial support, and decision-making power for women is critical to reducing poverty and advancing gender equity. These reforms aim to transform policy frameworks into actionable, inclusive solutions, ensuring Aceh’s poverty alleviation efforts align with the needs and contributions of its women.